Energetics based spike generation of a single neuron: simulation results and analysis - Venkateswaran, Nagarajan; Sekhar, Sudarshan; T.S, Thiagarajan; Navalpakkam Krishnan, Sharath; Kannan K, Dinesh; Ramanathan, Subbu; Narayanasamy, Naren; Jagathrakshakan, Sharan Srinivas; S. R, Vignesh (Frontiers in Neuroenergetics, 2012)
Existing current based models that capture spike activity, though useful in studying information processing capabilities of neurons, fail to throw light on their internal functioning. It is imperative to develop a model that captures the spike train of a neuron as a function of its intra cellular parameters for non-invasive diagnosis of diseased neurons. This is the first ever article to present such an integrated model that quantifies the inter-dependency between spike activity and intra cellular energetics. The generated spike trains from our integrated model will throw greater light on the intra-cellular energetics than existing current models. Now, an abnormality in the spike of a diseased neuron can be linked and hence effectively analyzed at the energetics level. The spectral analysis of the generated spike trains in a time-frequency domain will help identify abnormalities in the internals of a neuron. As a case study, the parameters of our model are tuned for Alzheimer disease and its resultant spike trains are studied and presented.